2021
DOI: 10.3390/ijms22136654
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Histone Deacetylase Inhibitors with Distinct Latency Reversing Agents Variably Affect HIV Reactivation and Susceptibility to NK Cell-Mediated Killing of T Cells That Exit Viral Latency

Abstract: The ‘shock-and-kill’ strategy to purge the latent HIV reservoir relies on latency-reversing agents (LRAs) to reactivate the provirus and subsequent immune-mediated killing of HIV-expressing cells. Yet, clinical trials employing histone deacetylase inhibitors (HDACis; Vorinostat, Romidepsin, Panobinostat) as LRAs failed to reduce the HIV reservoir size, stressing the need for more effective latency reversal strategies, such as 2-LRA combinations, and enhancement of the immune responses. Interestingly, several L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 81 publications
2
15
0
Order By: Relevance
“…In contrast, in vitro, it has been reported that histone deacetylase inhibitors up-modulate the expression of ligands such as NKG2D on NK cells. Thus, it is necessary for NKG2D-mediated viral suppression by NK cells [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in vitro, it has been reported that histone deacetylase inhibitors up-modulate the expression of ligands such as NKG2D on NK cells. Thus, it is necessary for NKG2D-mediated viral suppression by NK cells [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…They were followed up at 12 weeks and divided depending on the received scheme treatment, CT, and MT for this study. The median age for the CT group was 32 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) years and 34 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) years for MT group.…”
Section: Baseline Clinic Characteristics Of Study Populationsmentioning
confidence: 99%
“…Although LRAs are widely used in the treatment of virus reservoirs, some LRAs can be toxic and damage immune cells ( 121 , 122 ). Many recent studies have explored various LRAs that enhance NK cell function.…”
Section: Nk Cell–based Immune Interventions Provide a Promising Strat...mentioning
confidence: 99%
“…PRO, a protein kinase C agonist, activates NK cells and markedly increases CD69 and CD107a expression ( 122 ). PRO/romidepsin combination treatment was shown to enhance NKG2D-mediated NK cell killing of P24 targets compared with single-drug treatment ( 121 ). TLR agonists also reverse HIV latency and enhance innate antiviral immunity ( 124 ).…”
Section: Nk Cell–based Immune Interventions Provide a Promising Strat...mentioning
confidence: 99%
“…Clinical trials have shown that some LRAs can effectively activate latently infected cells, but are not able to reduce the size of the latent pool, possibly due to ineffective killing by the HIVspecific cytotoxic T lymphocyte (CTL) response. 45 The lack of specificity of LRAs, coupled with heterogeneity of the repository, leads to limitations in the treatment with LRAs. Therefore, although there have been many studies on the activation of latent reservoirs by various LRAs, there is still a need for screening of efficient and suitable LRAs.…”
Section: Challenges Of Classic Lras For Hiv Curementioning
confidence: 99%